2020
DOI: 10.3389/fmicb.2019.03112
|View full text |Cite
|
Sign up to set email alerts
|

The Endophyte Pantoea alhagi NX-11 Alleviates Salt Stress Damage to Rice Seedlings by Secreting Exopolysaccharides

Abstract: Endophytes have the potential to enhance the ability of plants to resist salt stress, improving crop development and yield. Therefore, in this study, we isolated an endophyte that produced large amounts of exopolysaccharides (EPSs) from the roots of sea rice and examined its effects on the physiological responses of rice (Oryza sativa L. ssp. japonica "Nipponbare") seedlings to salt stress using hydroponic experiments. The endophyte was named Pantoea alhagi NX-11 based on its morphological characteristics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 53 publications
2
46
0
Order By: Relevance
“…The increased activities of AEs and/or the elevated accumulations of osmoregulators in PGPB-inoculated plants were reported by Li and Jiang [ 42 ], Akram et al [ 45 ], Vaishnav et al [ 47 ], Khalid et al [ 58 ], Kim et al [ 96 ], Habib et al [ 97 ], Kang et al [ 104 ], Zhu et al [ 107 ], Halo et al [ 151 ], Bharti et al [ 152 ], El-Esawi et al [ 153 ], Vimal et al [ 154 ], El-Nahrawy and Yassin [ 155 ], Sun et al [ 156 ]. For instance, the activity of ROS-scavenging enzymes SOD, CAT of Enterobacter -treated okra plants was the highest amongst all treatments, in parallel with their highest vegetative parameters SFW, SDW, RFW, and RDW [ 97 ].…”
Section: Plant Growth-promoting Rhizobacteria As the Promising Biomentioning
confidence: 99%
“…The increased activities of AEs and/or the elevated accumulations of osmoregulators in PGPB-inoculated plants were reported by Li and Jiang [ 42 ], Akram et al [ 45 ], Vaishnav et al [ 47 ], Khalid et al [ 58 ], Kim et al [ 96 ], Habib et al [ 97 ], Kang et al [ 104 ], Zhu et al [ 107 ], Halo et al [ 151 ], Bharti et al [ 152 ], El-Esawi et al [ 153 ], Vimal et al [ 154 ], El-Nahrawy and Yassin [ 155 ], Sun et al [ 156 ]. For instance, the activity of ROS-scavenging enzymes SOD, CAT of Enterobacter -treated okra plants was the highest amongst all treatments, in parallel with their highest vegetative parameters SFW, SDW, RFW, and RDW [ 97 ].…”
Section: Plant Growth-promoting Rhizobacteria As the Promising Biomentioning
confidence: 99%
“…All assays were performed as described in Materials and Methods [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. Table 3 was constructed according to the estimates of response level of each bacterial strain to the applied beneficial traits (strong, medium, low, not applicable).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, maintaining the ecological balance of the agricultural ecosystems requires the imposition of drastic solutions to the problem [ 3 , 40 ]. Many studies prove the effect of PGPR on the alleviation of salt stress on crop plants [ 13 , 41 , 42 , 43 , 44 , 45 ]. Arthrobacter protophormiae (SA3) and Dietzia natronolimnaea (STR1) enhanced photosynthetic efficiency [ 42 ], IAA content and other beneficial traits in wheat, Klebsiella , Pseudomonas , Agrobacterium , and Ochrobactrum in peanut [ 43 ], Pseudomonas putida UW4 and P. migulae 8R6 effected on Camelina sativa (camelina) [ 44 ], Micrococcus yunnanensis , Planococcus rifietoensis , and Variovorax paradoxus on Beta vulgaris [ 45 ], Bacillus licheniformis AP6 and Pseudomonas plecoglossicida PB5 with proven biofilm formation can facilitate sunflower growth by improving physiological and biochemical attributes [ 46 ], Bacillus megaterium in Zea mays , Azospirillum sp.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Mahmood et al (2016) concluded that under salinity stress, treatment of mung bean with EPS producing Enterobacter cloacae and Bacillus drentensis enhanced nutrient availability and water uptake in plants by the formation of biofilm in the root zone. In another study, inoculation of EPS producing endophyte, Pantoea alhagi NX-11 improved salt tolerance of rice seedlings by improving the antioxidant activity resulting in better growth in comparison to the plants treated with EPS mutant NX-11 eps− (Sun et al, 2020). Likewise, treatment of maize with EPS producing Azotobacter chrococcum strains C5 and C9 under saline conditions alleviated the saline stress by several means i.e., increasing K + /Na + ratio and ions uptake (Na + , K + , Ca 2+ , Mg 2+ ), chlorophyll content, and accumulation of proline and polyphenols (Rojas-Tapias et al, 2012).…”
Section: Exopolysaccharides (Eps)mentioning
confidence: 98%